Write g(x) so that it is the inverse of the given function f(x). f(x) = 1/3x – 5/3 g(x) =

Write g(x) so that it is the inverse of the given function f(x). f(x) = 1/3x - 5/3 g(x) =

Related Posts

This Post Has 3 Comments

  1. 9514 1404 393

      g(x) = 3x +5

    Step-by-step explanation:

    The inverse function can be found by solving ...

      x = f(y)

      x = 1/3y -5/3 . . . . . use the definition of f(x)

      3x = y -5 . . . . . . . . multiply by 3

      3x +5 = y . . . . . . . .add 5

    Then the inverse function is ...

      g(x) = 3x +5

Leave a Reply

Your email address will not be published. Required fields are marked *